2021
DOI: 10.3389/fcvm.2021.701583
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation as a Therapeutic Target for Myocardial Infarction

Abstract: Myocardial infarction is a prevalent and life-threatening cardiovascular disease. The main goal of existing interventional therapies is to restore coronary reperfusion while few are designed to ameliorate the pathology of heart diseases via targeting the post-translational modifications of those critical proteins. Small ubiquitin-like modifier (SUMO) proteins are recently discovered to form a new type of protein post-translational modifications (PTM), known as SUMOylation. SUMOylation and deSUMOylation are dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 145 publications
0
10
0
Order By: Relevance
“…SUMOylation of proteins has emerged as an important therapeutic target for drug discovery 8 , 14 . We recently demonstrated that natural product puerarin protected cardiomyocytes against ischemia reperfusion injury via up-regulating SUMO2 and SUMOylation without altering SUMO1 expression 8 . The present study was designed to identify SUMO2-modified proteins and elucidate the cardioprotective mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SUMOylation of proteins has emerged as an important therapeutic target for drug discovery 8 , 14 . We recently demonstrated that natural product puerarin protected cardiomyocytes against ischemia reperfusion injury via up-regulating SUMO2 and SUMOylation without altering SUMO1 expression 8 . The present study was designed to identify SUMO2-modified proteins and elucidate the cardioprotective mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Timely intitiation of DNA repair is crucial to maintain genome integrity and enhance survival 58 . On the other hand, we recently proposed that SUMO2 might exhibit cardioprotective activity via increasing SUMOylation of specific proteins in myocardial infarction 8 . In the present study, firstly, we validated that the discrepancy in the intracellular localization of SUMO2 and γ-actin and the status of DNA damage in a mouse model of myocardial infarction and H9c2 cell model of hypoxia reoxygenation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, astragaloside IV promotes the proliferation and migration of vascular endothelial cells and antagonizes the adverse microenvironment of hypoxia and high glucose by enhancing SUMO1 expression in human umbilical vein endothelial cells (Wang B. S. et al, 2021). In cardiomyocytes, puerarin attenuates cellular inflammatory response and fibrosis through activating ER/ERK pathway by increasing the expression of SUMO2 (Zhao et al, 2021a). In oral squamous cell carcinoma cells, ginkgolic acid suppresses tumorigenicity and tumor progression through inhibition of the enhancement of SUMOylation of Smad4 (Liu et al, 2020).…”
Section: Natural Products Against Renal Fibrosis Via Regulating the S...mentioning
confidence: 99%
“…Myocardial infarction is a common cardiovascular disease of rapid onset ( Zhao et al, 2021 ). Current evidence suggests that although reperfusion can reduce cardiac tissue injury, it increases perfusion injury ( Zhang G. et al, 2021 ).…”
Section: Baicalin and Embryonic Stem Cellsmentioning
confidence: 99%